Fatal Graft-Versus-Host Disease Following Adult-To-Adult Living Donor Liver Transplantation From an HLA Nonhomozygous Donor. (December 2016) - Yu, Young-Dong; Kim, Dong-Sik; Ha, Neul; Jung, Sung-Won; Han, Jae-Hyun; Kim, Joo-Young; Park, Sung-Hwan; Cho, Yun-Jung
The use of a human leukocyte antigen (HLA) homozygous donor to a haploidentical recipient is a well-documented cause of transfusion-associated graft-versus-host disease (GVHD). Several authors have reported that use of a graft from an HLA-homozygous donor with 1-way donor-recipient HLA matching led to an extremely high risk of developing GVHD in LDLT. We have experienced a fatal case of acute GVHD following adult-to-adult LDLT from a donor who was heterozygous at a single HLA locus. A 53-year-old female underwent LDLT for chronic hepatitis B and recurrent hepatocellular carcinoma. The donor was her 23-year-old son. The HLA phenotype of the donor was not homozygous (A24, -; B54, -; DR4, 9) and revealed one-way donor-dominant HLA matching at two loci with the recipient (A2, 24; B48, 54; DR4, 12). On the fortieth postoperative day, the patient showed erythematous skin lesions. Skin biopsy revealed typical findings of GVHD. Donor-derived chimerism was demonstrated by performing fluorescent in situ hybridization (FISH) using the recipient's skin tissue. As the clinical course deteriorated, etanercept was started in addition to broad-spectrum antibiotics but there was no improvement. As multi-organ failure progressed, the patient succumbed to death on the 54th postoperative day, which was 2 weeks after onset of GVHD. The prevention of GVHD is more important since the results of treatment have been disappointing. We have experienced a fatal case of acute GVHD following adult-to-adult LDLT from a HLA non-homozygous donor. HLA heterozygosity at a single locus does not preclude the possibility of developing GVHD following adult-to-adult LDLT.